ELECTRONIC RESOURCES IN THE SCIENTIFIC AND TECHNICAL LIBRARY OF LVIV POLYTECHNIC TO ENSURE USER CONVENIENCE AND EFFICIENCY - SOKIL, MARIIA; ZVORSKYI, ANDRII (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The paper explores the impact of electronic services on library users. The paper highlights the importance of implementing electronic services in libraries, which allows users to conveniently and efficiently obtain the necessary information and services. The article presents the results of studies that confirm that electronic services enable users to quickly and efficiently find the required information, access electronic resources, order documents, and other library services. The authors also draw attention to the need to prepare users to use electronic library services and to develop a culture of electronic communication among library staff. The article concludes that using electronic services in libraries allows users to have quick and convenient access to the necessary information and services, increasing the library's efficiency and user satisfaction.
Keywords: Internet resources; information resources; popularization; electronic services; library resources